SUGAR BEET CULTIVATION IN THE ECONOMY OF AGRICULTURAL ENTERPRISES - Чирва, І. В. (Scientific Progress & Innovations, 2015)
Modern conditions of development of sugar beet production in farms of Poltava region and Ukraine have been given in the article. The problems of reduction of sowing areas, productivity increase, fluctuation of level of income and profitability have been found out. The dynamics of costs on the production of sugar beets at agricultural enterprises has been analyzed. The recommendations concerning management of costs on sugar beet growing in the region on account of purchase of domestic seeds and machines have been brought. Propositions for the increase of industry efficiency have been offered.